Prediction of the maternal and perinatal outcomes in premature rupture of membranes at and after 37 weeks of gestation using maternal serum C reactive protein levels - Bharti, Pratima; Dheeraj, Sarita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Premature rupture of membranes (PROM) complicates 5-10% of pregnancies, mostly at term, and increases the risk of maternal and neonatal morbidity due to intrauterine infection. Early prediction is crucial, and C-reactive protein (CRP), an acute-phase reactant, is frequently studied, though its diagnostic accuracy in PROM remains uncertain. This study was conducted to evaluate the role of maternal serum CRP in predicting chorioamnionitis and associated complications in term PROM. Methods: This prospective observational study included 90 women with term PROM admitted to Swami Dayanand Hospital, New Delhi, between August 2022 and February 2024. Maternal serum CRP was measured at admission, and patients were followed for development of chorioamnionitis, mode of delivery, and maternal and neonatal outcomes. Diagnostic accuracy was calculated. Results: Of 90 women, 72% were aged 21-30 years and 65.6% were primigravida; mean gestational age was 38.4 weeks. Adverse outcomes were significantly higher with leaking >24 hours (p=0.008). CRP ≥5 mg/L was associated with caesarean delivery (35.1% vs. 11.3%, p=0.02), postpartum febrile morbidity (32.4% vs. 7.5%, p=0.004), and neonatal antibiotic requirement (35.1% vs. 11.3%, p=0.006). No significant association was observed with chorioamnionitis, postpartum haemorrhage, low Apgar scores, neonatal intensive care unit (NICU) admission, or perinatal death. CRP predicted adverse outcomes with 64.7% sensitivity, 73.2% specificity, and 70% diagnostic accuracy. Conclusions: Maternal CRP ≥5 mg/L is a useful predictor of adverse outcomes in term PROM, particularly postpartum infection and neonatal sepsis risk. Its high negative predictive value supports its role as a simple, cost-effective screening tool.